Electronic design and validation of Powered Knee Orthosis system embedded with wearable sensors - Felix, Paulo (2017)
The development of new architectures for orthotic devices has been playing a major role in the rehabilitation of gait disorders. This paper proposes a new electronic and control architecture for a powered orthosis, particularly, a knee orthosis. The system was designed to be modular, being composed of the orthosis and biomedical wearable sensors, such as inertial measurement units, force sensitive resistors, and electromyography. For each component, robust hardware and software interfaces were designed and validated, plus two tracking control strategies, namely, position control, that imposes a trajectory based on the angle measured in the joint, and torque control to act mostly as a passive component, using the measured user-orthosis interaction torque. The whole system was validated with healthy subjects walking in level-ground on a treadmill at different speeds. The main results show that the system is functional. The interfaces created as well as the assistive control techniques were successfully validated. Moreover, the system allows an efficient inclusion of other devices, given the modularity achieved in its design.